The Effect of English Authentic Youtube Videos on Students' Speaking Skills in Rural School - Muslem, Asnawi; Fata, Ika Apriani; Saputri, Windy Ilan (Universitas Pendidikan Ganesha, 2022)
Technology expands students' opportunities for authentic interaction with native speakers and other language learners at various levels, both inside and outside of the classroom. The purpose of this research is to examine an improvement in students' speaking skills in terms of fluency, vocabulary, grammar, pronunciation, and accuracy by using English YouTube videos, as well as the impact on students' speaking skills with a civil and non civil servant's family background in rural school. In this study, a quantitative method with a true experimental design was used, and a total of N=90 students participated, with N=50 students chosen using purposive sampling from two different classes to serve as samples. The instrument for the study included tests, a pre-test, and a post-test. The data was then analysed statistically to determine the results of the given pre-test and post-test. The average score increased after the post-test in terms of receiving results in terms of improving students' English speaking. Accuracy turned out to be one of the most important aspects of speaking that improved markedly. It means that students learned from native speakers through English YouTube videos, and their accuracy has enormously improved as a result. Meanwhile, students from civil servant families scored 95 on the post-test, while students from non-civil servant families scored 92.5. It was discovered that there is only a minor difference in improvement between civil and non-civil servant students' backgrounds. Teachers should consider using authentic English YouTube videos in the classroom to assist children of their English speaking skills.